2017
DOI: 10.1159/000455027
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastatic Disease in Pancreatic Cancer - How to Proceed

Abstract: Background: Pancreatic cancer is a highly aggressive malignancy and will become the second leading cause of cancer-related death in the USA and also in Germany by 2030. Furthermore, the majority of patients with pancreatic ductal adenocarcinoma (PDAC) will present with distant metastases, limiting surgical management in this population as there is little evidence available to support surgical or ablative treatment options for advanced-stage disease. However, highly selected patients suffering from synchronous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Surgical resection remains the only potentially curative therapy, but most PDAC patients are diagnosed at advanced stages and miss their chance for operation [3,4]. This disappointing outcome is partly due to the uncontrolled rapid tumor growth and invasion of PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection remains the only potentially curative therapy, but most PDAC patients are diagnosed at advanced stages and miss their chance for operation [3,4]. This disappointing outcome is partly due to the uncontrolled rapid tumor growth and invasion of PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…New chemotherapeutic regimens also significantly prolong the survival of PDAC patients with metastatic tumors 7,8 . Thus, especially in the context of multimodal therapies, surgery for PDAC patients with metastasis, especially those with oligometastatic and metachronous disease, has gained interest 9,10 . Several studies have reported that for selected cases with distant metastasis, resection might relevantly prolong survival, compared to palliative treatment 9-11 . In this study, we utilized the surveillance, epidemiology, and end results (SEER) program database and relevant reported clinical studies and case series to comprehensively generate evidence of the impact of surgery for PDAC patients with distant metastasis.…”
mentioning
confidence: 99%
“…The feasibility and safety of combined pancreatectomies and liver resections has been already demonstrated (95). Actually most patients resected for M1 liver PDAC reported in the literature underwent wedge/atypical only liver resections (96)(97)(98).…”
Section: Resection For M1 Pdacmentioning
confidence: 98%
“…Interestingly, a recent multicentric study has shown that the overall survival is significantly higher in patients with oligometastatic M1 PDAC of the head who underwent resection, compared with bypass, while for M1 PDAC of the body and tail no differences were observed (102). Recent reviews of the literature have shown that resection for M1 liver PDAC might have a survival benefit in carefully selected patients, particularly with metachronous metastases (96,98).…”
Section: Resection For M1 Pdacmentioning
confidence: 99%